Mental wellbeing in bereaved carers: A Health Survey for England population study. Issue Volume 12:Issue e4(2022) (6th September 2019) - Hodiamont, Farina; Allgar, Victoria; Currow, David C; Johnson, Miriam J
Abstract : Objectives: The experience of caregiving may affect carers' well-being into bereavement. We explored associations between mental well-being and previous experience of bereavement of, and caring for, someone close at the end-of-life. Methods: An end-of-life set of questions was included in population-based household survey administered to adults (age 16 years and above). We used univariable regression to explore the cross-sectional relationship between our primary outcome (Warwick-Edinburgh Mental Well-being Scale (WEMWBS)) and possible explanatory variables: sociodemographic; death and bereavement including ability to continue with their life; disease and carer characteristics; service use and caregiving experience. Results: The analysis dataset included 7606 of whom 5849 (77%) were not bereaved, 1174 (15%) were bereaved but provided no care and 583 (8%) were bereaved carers. WEMWBS was lower in the oldest age class (85 years and above) in both bereaved groups compared with not bereaved (p<0.001). The worst WEMWBS scores were seen in the 'bereaved but no care' group who had bad/very bad health self-assessed general health (39.8 (10.1)) vs 41.6 (9.5)) in those not bereaved and 46.4 (10.7) in bereaved carers. Among the bereaved groups, those who would not be willing to care again had lower WEMWBS scores than those who would (48.3 (8.3) vs 51.4 (8.4), p=0.024). Conclusion: Mental well-being in bereavement was worse in people with self-reported poor/very poor general health and those with a worse caregiving experience. Although causality cannot be assumed, interventions to help people with worse mental and physical health to care, so that their experience is as positive as possible, should be explored prospectively.